Prevalence and sources of stress among hospital training pharmacy students in Universiti Teknologi Mara - Ab Aziz, Nusaibah (2015)
In this modernised world, people are more aware of the importance of health in our life. As stated in The World Health Organization (WHO) “Health is a state of complete physical, mental, and social well-being and not merely the absence of disease or infirmity”(WHO, 1946) and “mental health can be defined as a state of well-being enabling people to realize their abilities, cope with normal stresses of life, work productively and fruitfully, and make contribution to their communities.” (WHO, 2014). Mental health of a person related closely to the stress contributes to them. Stress is a term often used by individuals in a variety of social, academic and employments setting (Marshall, Allison, Nykamp, & Lanke, 2008).